2014
DOI: 10.1139/cjes-2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic and chronologic analysis of the Warren Beach, northwest Ohio, USA

Abstract: The current understanding of Lake Warren as a proglacial lake stage in the Lake Erie basin during the last deglaciation is based on limited stratigraphic information from strandlines and a wide range of radiocarbon ages. The purpose of this study is to use ground-penetrating radar (GPR) and optically stimulated luminescence (OSL) dating to reconstruct the stratigraphy, depositional environment, and age of the Oak Openings Ridge (OOR), a former strandline of Lake Warren in northwestern Ohio. Both sedimentary ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…In areas that are predominantly flat, or lack significant topographic relief, the three Warren shorelines can be easily distinguished; otherwise the lowest Warren strandline tends to blend with the middle Warren due to its low cresting elevation (Totten, 1985). The Warren strandlines have a higher sand volume than older beaches (Whittlesey) and form large barrier island and spit complexes in southern Michigan and northern Ohio (e.g., Calkin and Feenstra, 1985;Totten, 1985;Higley et al, 2014). Lake Warren is constrained from a series of dates that bracket the relative age of the beaches.…”
Section: Lake Warrenmentioning
confidence: 99%
See 4 more Smart Citations
“…In areas that are predominantly flat, or lack significant topographic relief, the three Warren shorelines can be easily distinguished; otherwise the lowest Warren strandline tends to blend with the middle Warren due to its low cresting elevation (Totten, 1985). The Warren strandlines have a higher sand volume than older beaches (Whittlesey) and form large barrier island and spit complexes in southern Michigan and northern Ohio (e.g., Calkin and Feenstra, 1985;Totten, 1985;Higley et al, 2014). Lake Warren is constrained from a series of dates that bracket the relative age of the beaches.…”
Section: Lake Warrenmentioning
confidence: 99%
“…A recent study by Campbell (2009) dated wood fragments found in a littoral drift unit of the Oak Openings Ridge between 14,507 to 13,921 cal years BP (13,430 ± 90 14 C yrs BP); the reworked wood fragments provide a more reliable maximum age for Lake Warren in the Erie Basin (Campbell, 2009). Recent work from Higley et al (2014) obtained an OSL age for Lake Warren of 14.1 ± 1.1 ka.…”
Section: Lake Warrenmentioning
confidence: 99%
See 3 more Smart Citations